Cholesterol is Involved in Tumorigenesis and Its Potential Therapeutic Prospects - Yang Xi; Zhou Yani; Mao Jing; Wu Yinhang; Hou Xiaohui; Zhuang Jing; Qi Quan; Han Shuwen (Novel Aspects on Pharmaceutical Research Vol. 5, 2023)
This chapter will help citizens realize the important function of cholesterol during tumor formation as well as the importance of adjusting their diets, have a healthy lifestyle, and of physical fitness. Tumor cells are characterized by rapid growth and infinite replication potential; thus, their high energy and biosynthesis requirements need to be satisfied, particularly the biosynthesis of cell membranes. Recent studies have shown that cholesterol, an essential component of cell membranes, has a significant impact on the development of tumours, immune system dysregulation, and pathological changes in epigenetic mechanisms. Cholesterol biosynthesis is an extremely common phenomenon in organisms, the process is complicated. There is a increasing interest on targeting cholesterol in the treatment of cancer. First, it was comprehensively reviewed the major function of cholesterol on oncogenicity, the therapeutic targets of cholesterol and its metabolites in cancer, and provide detailed insight into the essential roles of cholesterol in mediating immune and epigenetic mechanisms of the tumor microenvironment. It is believed that cancer cells tolerate excessive metabolic consequences of plasma cholesterol intake to sustain cancer progression, which may explain why the level of serum cholesterol in some cancer patients is normal or even below normal ranges. Additionally, due to its function in cholesterol metabolism, the gut microbiome is an essential part of cancer mediation. To provide more therapeutic interventions in oncology, the most recent research on the potential targets of cholesterol and their metabolism was summarised.